Information and Communication Technology Use Capacity Within Extension Networks: Development and Preliminary Validation of an Empirical Scale - Kevan W. Lamm; Kristin Davis; Catherine E. Sanders; Alyssa Powell (Journal of International Agricultural and Extension Education, 2021)
Advancing information and communication technologies (ICTs) has become central to international agricultural and extension development efforts. ICTs are crucial in facilitating information transfer, ensuring stakeholder access to information, and increasing the decision-making capacity of smallholder farmers. The research presented here introduces an instrument developed to quantify perceptions of ICT use capacity within international extension networks. The aggregate scale was verified for content validity, response process validity, internal structure validity, and consequential validity informing its use. The instrument was administered to network members (n = 122) associated with the Global Forum for Rural Advisory Services. An exploratory factor analysis (EFA) was conducted with measures of correlation and reliability analyzed. Six factors were extracted and analyzed further. The resulting Perceptions of ICT Use scale and factors can be used as reliable instruments for quantifying perceptions of ICT use capacity, enhancing international extension network needs assessments, and informing policies and practices which maximize ICT capacity.
Keywords: information communication technology (ICT); scale development; rural advisory services; international extension; capacity assessment